Pengaruh Kinerja Keuangan Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan GCG Sebagai Variabel Moderasi - Arianti Latif; Jumawan Jasman; Asriany Asriany (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the effect of financial performance and company size on corporate value with good corporate governance as a moderating variable. This type of research is quantitative research. The population in this study were restaurant, hotel and tourism companies listed on the Indonesia Stock Exchange for the 2018-2021 period with a total of 47 companies observed. The sampling technique used was purposive sampling based on certain criteria. Testing research data using multiple regression analysis and also using Moderate Regression Analysis (MRA). Based on the results of research on financial performance has no significant effect on firm value. Firm size has a significant effect on firm value. Good Corporate Governance is not able to moderate the relationship between financial performance and company value. Good Corporate Governance is able to moderate the relationship between company size and company value.